Axitinib in sequential therapy in metastatic renal cell carcinoma - Kuchar, Agata; Hryciuk, Beata; Stec, Rafał; Mączewski, Michał; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2016)
Efficacy of new molecularly targeted drugs in the treatment of renal cell carcinoma (RCC), confirmed in clinical studies in relation to survival and prolongation of time to progression, has became a big chance for patients with metastatic renal cell cancer. Axitinib is a potent and selective receptor tyrosine kinase for vascular endothelial growth factor (VEGFR-1, -2, -3), platelet-derived growth factor  (PDGRF-) and c-KIT. This is a case report of a 57-year old female patient with a history of left nephrectomy due to clear cell renal cell carcinoma. The patient had received three prior systemic treatments (interferon – sorafenib – everolimus). After consecutive progression the patient was qualified to 4th line therapy – axitinib at a dose of 5 mg twice daily. Partial response to treatment was achieved. After 6 months therapy was stopped due to the disease progression. The total time to progression was 37.5 months. The total survival time from the disease diagnosis was 45 months. Based on literature date and own experience we showed that sequential treatment RCC is associated with improved survival. In summary, axitinib may be an effective drug after failure of tyrosine-kinase inhibitor (TKI) therapy in previous lines of therapy.